Du malentendu à la coopération: la France, l’Italie et l’entrée de l’Espagne dans la Communauté européenne (1979-1985) - Lella, Giovanni (Studi Politici, 2023)
This article explores the role played by France and Italy in the negotiations for Spain’s accession to the European Community. As Mediterranean countries with a strong agricultural sectors, Italy and France were among the member countries most concerned by Spain’s entry into the common market. Based on French and Italian archives, this paper seeks to demonstrate how cooperation between the two countries, which was not granted at the beginning of the discussions, finally proved crucial in breaking the deadlock in negotiations. The article is structured in three parts. In the first part, it deals with the difference in approach between Rome and Paris on the issue, so the misunderstandings that arose from it; in the second part, it examines the factors that led to a first clarification between the two countries; finally, it focuses on the cooperation set up by Mitterrand’s France and the Craxi-Andreotti tandem in order to finish the job and mark an important step towards the relaunch of Europe.